트랜스 미디어 콘텐츠에서의 VR 애니메이션 특성 연구 - 암묵적 편집 개념 적용 - 권동현(Dong-Hyun Kwon) (디지털콘텐츠학회논문지, 2020)
실시간 인터랙티브 3D애니메이션으로 구현되는 VR콘텐츠는 이용자가 가상 공간속에서 관객이 아닌 주체가 되는 경험을 한다. VR콘텐츠는 스토리 감상, 어트랙션, 탐험과 같은 다양한 콘텐츠 형식으로 제작되어 기존 매체들로 구성된 트랜스 미디어 콘텐츠 집합체 속에서 새로운 역할을 담당할 수 있다. 프레임이 없는 VR콘텐츠는 영상 역사 100년 동안 다듬어진 편집문법이 아닌 새로운 개념을 요구한다. 이에 연구자는 실시간 인터랙티브 애니메이션으로 구현되는 VR콘텐츠에서 편집 개념으로 적용할 수 있는 암묵적 편집 개념을 구상하고 이를 적용하여 그동안 출시된 트랜스 미디어 VR콘텐츠 사례를 살펴보았다. VR콘텐츠를 스토리 3대 요소인 인물, 사건, 배경으로 분석한 결과 인물과 사건 면에서 새로운 경험을 전개할 수 있는 매력적인 매체라 할 수 있으나, 배경 면에서는 비용을 고려할 때 신중한 진행이 필요하며, 가장 일반화 된 프랜차이즈 트랜스 미디어 형태 보다는 기획 단계부터 함께 개발하는 네이티브 트랜스 미디어 콘텐츠로서 진행하는 것이 합리적인 방향임을 알 수 있었다. VR contents implemented by real-time interactive 3D animation experience users in virtual space as subjects rather than audiences. VR content is produced in a variety of content formats such as story appreciation, attractions, and exploration, and can play a new role in the collection of transmedia content composed of existing media. VR content without frames requires a new concept, not the editorial grammar that has been refined for 100 years of video history. Accordingly, the researcher conceived an implicit editing concept that can be applied as an editing concept in VR content implemented with real-time interactive animation and applied it to look at cases of transmedia VR content released so far. As a result of analyzing VR contents with the three main elements of the story, people, events, and backgrounds, it can be said that it is an attractive medium that can unfold new experiences in terms of people and events. It can be seen that it is a reasonable direction to proceed as native transmedia contents developed together from the planning stage rather than a generalized franchise transmedia form. KCI Citation Count: 5